Advances in Antifungal Development: Discovery of New Drugs and Drug Repurposing - Kim, Jong Heon; Cheng, Luisa W.; Land, Kirkwood (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This reprint describes recent advances made in the field of antifungal development, especially the discovery of new drugs and drug repurposing. The articles presented in this book provide useful information and insight for the development of new antifungal drugs or intervention strategies. The identification of new, safe molecules, and cellular targets, as well as the elucidation of their antifungal mechanisms of action, will further the effective control of fungal pathogens, especially those resistant to current therapeutic agents.